Analisis Kualitas Perairan Bozem FMIPA UNESA Berdasarkan Parameter Fisika Kimia - Fahmi Nasrullah Azmi; Herlina Fitrihidajati (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
The Bozem at the Faculty of Mathematics and Natural Sciences (FMIPA), Surabaya State University (UNESA), is an artificial body of water that serves as a water reservoir while also supporting ecological functions on campus. The water quality in the pond is susceptible to deterioration due to the influx of organic matter from rainwater runoff and surrounding activities. This study aims to analyze the status of the water in the UNESA FMIPA pond by examining physical and chemical parameters, namely temperature, transparency, turbidity, Total Dissolved Solids (TDS), pH, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), and CO₂ levels, and comparing them with the Class II lake water quality standards as stipulated in Government Regulation No. 22 of 2021. The study employed a quantitative descriptive method using field surveys as its approach. The data were analyzed descriptively and comparatively by comparing the water quality standards with the applicable measurement results. The results of the study indicate that most water quality parameters still meet the quality standards. Water temperature deviated by 1°C from air temperature; the average TDS was 234 mg/L, pH was 8.6, DO was 7.4 mg/L, BOD was 2.5 mg/L, and CO₂ was 3.74 mg/L. Low transparency (0.25 m) and high turbidity (61.9 NTU) indicate a high concentration of suspended particles in the water. Overall, the water quality of Bozem FMIPA UNESA still meets the Class II lake water quality standards as stipulated in Government Regulation No. 22 of 2021.